Endurance Training Intensity Does Not Mediate Interference to Maximal Lower-Body Strength Gain during Short-Term Concurrent Training - Fyfe, Jackson J.; Bartlett, Jonathan D.; Hanson, Erik D.; Stepto, Nigel K.; Bishop, David J. (Frontiers in Physiology, 2016)
We determined the effect of concurrent training incorporating either high-intensity interval training (HIT) or moderate-intensity continuous training (MICT) on maximal strength, counter-movement jump (CMJ) performance, and body composition adaptations, compared with single-mode resistance training (RT). Twenty-three recreationally-active males (mean ± SD: age, 29.6 ± 5.5 y; "V" ̇"O" 2peak, 44 ± 11 mL∙kg-1•min-1) were ranked by one-repetition maximum (1-RM) leg press strength and randomly allocated tounderwent 8 weeks (3 sessions•wk-1) of either: 1) HIT combined with RT (HIT+RT group, n=8), 2) work-matched MICT combined with RT (MICT+RT group, n=7), or 3) RT performed alone (RT group, n=8). Measures of aerobic capacity, maximal (1-RM) strength, counter-movement jump (CMJ) performance and body composition (DXA) were obtained before (PRE), mid-way (MID), and after (POST) eight weeks of training. Maximal (one-repetition maximum [1-RM]) leg press strength was improved from PRE to POST for RT (mean change ±90% confidence interval; 38.5 ±8.5%; effect size [ES] ±90% confidence interval; 1.26 ±0.24; P<0.001), HIT+RT (28.7 ±5.3%; ES, 1.17 ±0.19; P<0.001) and MICT+RT (27.5 ±4.6%, ES, 0.81 ±0.12; P<0.001); however, the magnitude of this change was greater for RT vs. both HIT+RT (7.4 ±8.7%; ES, 0.40 ±0.40) and MICT+RT (8.2 ±9.9%; ES, 0.60 ±0.45). There were no substantial between-group differences in 1-RM bench press strength gain. RT induced greater changes in peak CMJ force vs. HIT+RT (6.8 ±4.5%; ES, 0.41 ±0.28) and MICT+RT (9.9 ±11.2%; ES, 0.54 ±0.65), and greater improvements in maximal CMJ rate of force development (RFD) vs. HIT+RT (24.1 ±26.1%; ES, 0.72 ±0.88). Lower-body lean mass was similarly increased for RT (4.1 ±2.0%; ES; 0.33 ±0.16; P=0.023) and MICT+RT (3.6 ±2.4%; ES; 0.45 ±0.30; P=0.052); however, this change was attenuated for HIT+RT (1.8 ±1.6%; ES; 0.13 ±0.12; P=0.069). We conclude that concurrent training incorporating either HIT or work-matched MICT similarly attenuates improvements in maximal lower-body strength and indices of CMJ performance compared with RT performed alone. This suggests endurance training intensity is not a critical mediator of interference to maximal strength gain during short-term concurrent training.